Exploring the Impact of Imaging Resolution and Sharpness on Dermatological Diagnostics Using eSFR Measurements - Dugonik, Bogdan; Golob, Marjan (Elektronika ir Elektrotechnika, 2025)
High-resolution, small-form-factor image sensors enable the integration of mobile device cameras, which are increasingly being used for photographic documentation in many fields, including medicine. With the interface and handheld dermatoscopy, the smartphone camera forms an alternative tool to professional dermatoscopic systems for performing teledermatology and teledermoscopy. For the accurate diagnosis of skin diseases, image quality is essential, with sharpness and resolution being essential criteria. This paper focusses on measuring the sharpness and resolution of cameras used for image acquisition in dermatology using the spatial frequency response (SFR) method, which is based on standardised test charts featuring characteristic slanted contrast edges, known as edge SFR (eSFR) charts. The images were captured with mirrorless and DSLR cameras, smartphones, and a professional dermatoscopy video camera under typical dermatological conditions with digital cameras, mobile phones, and professional video dermatoscopes. Captured images were analysed, and the modulation transfer function (MTF) was defined to evaluate the performance of different camera optical systems applied for dermatological imaging. The results provide insight into the strengths and limitations of the various imaging devices and highlight their effectiveness in meeting the requirements of dermatological practice.